Broadening the Justifications for Inclusive Conservation: Values Associated With Nature’s Contributions to People - Gross, Milena; Wehrden, Henrik von; Mwampamba, Tuyeni Heita; Sanya, John; Pearson, Jasmine; Sesabo, Jennifer Kasanda; Riechers, Maraja; Arbieu, Ugo; Böhning-Gaese, Katrin (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Overlooking the diverse values associated with Nature's Contributions to People (NCP) undermines conservation efforts. To examine this underresearched association, we combined the NCP and plural valuation frameworks to investigate how values are associated with groups of people with shared NCP preferences, referred to as NCP preference clusters. We conducted 623 surveys with 362 farmers, 50 nature conservationists, 55 tour guides, and 156 tourists within the social–ecological system (SES) of Mount Kilimanjaro, Tanzania, comprising a national park as well as inhabited and cultivated areas. We identified five distinct clusters, each expressing varying degrees of intrinsic, instrumental, and relational values. While each framework overlooks key dimensions of people–nature relationships, combining both frameworks better captures the multidimensionality of such relationships and provides pivotal insights for inclusive conservation. To recognize the distinct associations between NCP preferences and diverse values, diversifying place-based conservation approaches in SESs with (a) protected area(s), without compromising biodiversity and ecosystem functioning, is pivotal.
Keywords: Inclusive Conservation; Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES); Relational Value; Stakeholder; Value Pluralism